Pengaruh Pengetahuan Kewirausahaan, Kualitas, dan Inovasi terhadap Keberhasilan Usaha Kayu Jati di Kabupaten Blora - Maulidia Umroatul Azizah; Ahmad Sehabuddin (Journal of Economics, Management, and Accounting, 2025)
This study aims to determine the influence of entrepreneurial knowledge, product quality, and product innovation on the success of teak wood MSMEs in Blora Regency. Teak wood MSMEs are a leading sector in the region with high growth potential, but they still face various challenges in maintaining their existence. This study employs a quantitative approach based on the Resource-Based View (RBV) theory developed by Edith Penrose in 1959 in her book The Theory of the Growth of the Firm. The research subjects are the owners of teak wood SMEs in Blora Regency, with a population of 141 individuals and a sample size of 104 individuals. Data collection was conducted using questionnaires, and data analysis was performed using multiple linear regression with the assistance of SPSS 26. The results of the study indicate that entrepreneurial knowledge influences business success by 14.36%, product quality by 7.50%, and product innovation by 11.08%. These findings indicate that enhancing the capacity of business operators through entrepreneurship training and product innovation is crucial. Additionally, support from the Blora Regency SME Agency contributes to business success. The researcher recommends that SME operators actively participate in management and entrepreneurship training to promote business growth and sustainability.